The Effect of Fruit Audio Aroma Media on Elementary Students’ Storytelling Ability - Egita Widya Astuti; Idam Ragil Widianto Atmojo; Septi Yulisetiani (STAI Hubbulwathan Duri, 2023)
This study aimed to examine the impact of Fruit Audio Aroma media on the narrative proficiency of third-grade students in an Indonesian Elementary School. The participants of this study were third-grade students from Karangasem 2 Public Elementary School. The study employed cluster random sampling as a method for selecting the sample. This study employed a one-shot case design to investigate the effects of administering the Fruit Audio Aroma therapy through media. The research employed a performance test as the data collection technique. The data analysis technique employed was non-parametric hypothesis testing, namely the Wilcoxon test. The data analysis technique was carried out by testing the non-parametric hypothesis, namely the Wilcoxon test. The results of the hypothesis test showed that the sig. (2-tailed) 0.05 means that H0 was rejected. This showed that the Fruit Audio Aroma media influenced the ability of the third-graders of elementary school students to tell stories.